The Influence of Scope, Frames, and Extreme Willingness to Pay Responses on Cost of Crime Estimates - Lee, Jacqueline G. (American journal of criminal justice, 2020)
As governments with limited fiscal resources seek to invest in the “best” programs to prevent crime, they often first try to identify the true costs of crime to guide these decisions. Contingent valuation (CV) is a common survey method used to elicit how much the public is willing to pay (WTP) to reduce a particular crime. We utilize one of the first datasets in criminal justice that includes open-ended WTP data gathered from a survey using factorial design and random assignment. WTP figures are then input into a formula which also takes into account 1) the number of households and 2) the number of crimes “avoided,” which is calculated based upon the percentage crime reduction presented to survey respondents. Drawing upon data from a representative sample of the United States, we assess how sensitive respondents are to crime type, crime reduction percentages, program types, and framing. Results demonstrate that in general, open-ended WTP surveys elicit highly skewed responses and that respondents are more willing to pay for crime reduction programs with a higher number of individual components. However, respondents are not sensitive to crime reductions or several other survey framing techniques. Importantly, due to these highly skewed WTP values and lack of responsivity to crime control percentages, final cost of crime numbers vary widely – potentially altering policy decisions driven by these methods. We conclude with a discussion of the appropriateness of these methods for accurately estimating the costs of crime.